2022
DOI: 10.3390/jpm12060919
|View full text |Cite
|
Sign up to set email alerts
|

Targeted RNAseq Improves Clinical Diagnosis of Very Early-Onset Pediatric Immune Dysregulation

Abstract: Despite increased use of whole exome sequencing (WES) for the clinical analysis of rare disease, overall diagnostic yield for most disorders hovers around 30%. Previous studies of mRNA have succeeded in increasing diagnoses for clearly defined disorders of monogenic inheritance. We asked if targeted RNA sequencing could provide similar benefits for primary immunodeficiencies (PIDs) and very early-onset inflammatory bowel disease (VEOIBD), both of which are difficult to diagnose due to high heterogeneity and va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 117 publications
(140 reference statements)
0
2
0
Order By: Relevance
“…This makes RNAseq data unique since both gene expression levels and pathogenic variants can be identified from the same sample (Zhao, 2019). Different studies in the literature have already reported the application of variant discovery from RNAseq data in different diseases (Berger, et al, 2022; Tushir, et al, 2021). However, the use of genomic and transcriptomic information content of RNAseq data together to generate condition-specific genome-scale metabolic models have remained unexplored to date.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This makes RNAseq data unique since both gene expression levels and pathogenic variants can be identified from the same sample (Zhao, 2019). Different studies in the literature have already reported the application of variant discovery from RNAseq data in different diseases (Berger, et al, 2022; Tushir, et al, 2021). However, the use of genomic and transcriptomic information content of RNAseq data together to generate condition-specific genome-scale metabolic models have remained unexplored to date.…”
Section: Introductionmentioning
confidence: 99%
“…This makes RNAseq data unique since both gene expression levels and pathogenic variants can be identified from the same sample (Zhao, 2019). Different studies in the literature have already reported the application of variant discovery from RNAseq data in different diseases (Berger, et al, 2022;Tushir, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%